Recent and future climate extremes arising from changes to the bivariate distribution of temperature and precipitation in Bavaria, Germany - Estrella, Nicole; Menzel, Annette (International journal of climatology, 2013)
ABSTRACT This study assesses recent and future changes in joint temperature and precipitation regimes at 28 sites in Bavaria, based on statistical downscaling of the ECHAM4 B2 Scenario (WETTREG). Monthly meteorological data of three future decades (2021–2030, 2031–2040 and 2041–2050) were compared with modelled data for the reference period 1971–2000. The bivariate data were classified into four weather types or modes (cooler/drier, cooler/wetter, warmer/wetter and warmer/drier relative to the 1971–2000 reference period). For the three future decades, a systematic change at all locations throughout the year was revealed. Both the cooler modes are predicted to occur less frequently in future decades; changes in warmer modes differ seasonally: In winter months, they are predicted to occur in the warmer/wetter mode, whereas in spring and summer months in the warmer/drier mode. Climatological extremes were defined as monthly weather events outside the 90% confidence ellipse of a Gaussian model of events in the reference period. An increase of extremes in the decade 2041–2050 was striking for June, which is predicted to be warmer and drier for half of the years. The same decade is predicted to experience the most extreme warm and wet modes, one in three Februarys and one in two winters are likely to be in this mode. The magnitude of these future changes in climate was related to the present mean annual temperature of the stations by rank regression. Stations with currently cooler climates are more likely to retain the normal conditions of the baseline period in contrast to currently warmer stations where the increase of extreme warm and wet conditions in summer and winter is expected to be larger. Copyright © 2012 Royal Meteorological Society